Evaluation of Macular and Peripapillary Blood Flow in Response to Intraocular Pressure Reduction in Patients With Posner–Schlossman Syndrome - Dan Liu; Dan Liu; Dan Liu; Cong Fan; Cong Fan; Cong Fan; Endong Zhang; Endong Zhang; Endong Zhang; Jie Yang; Jie Yang; Jie Yang; et al. (Frontiers in Physiology, 2022)
Purpose: The study aimed to evaluate the effect of intraocular pressure (IOP) reduction on macular and peripapillary microcirculation in patients with Posner–Schlossman syndrome (PSS) by optical coherence tomography angiography (OCTA).Methods: A prospective comparative study was conducted. Patients diagnosed with PSS at the Eye Center of Xiangya Hospital, Central South University, from February 2020 to November 2021 were consecutively included. OCTA was used for the macular and peripapillary microcirculation measurements, and optical coherence tomography (OCT) was employed for the retinal nerve fiber layer (RNFL) and lamina cribrosa depth (LCD) measurements. The patients received OCT and OCTA examinations at baseline and 1 week post-treatment when the IOP was under control. Changes in macular and peripapillary microcirculation, RNFL, and LCD were calculated for all the analyzed areas.Results: Twenty-one eyes from 21 patients were included in the study. Pre-treatment and post-treatment IOP were 43.17 ± 10.36 mm Hg (range, 30–60 mm Hg) and 17.17 ± 2.85 mm Hg (range, 13–23 mm Hg), respectively. No statistically significant changes were detected in RNFL, LCD, or macular and peripapillary microcirculation after significant IOP reduction.Conclusion: The results suggested that a large IOP reduction may not result in a significant increase in peripapillary and macular capillary perfusion in patients with PSS.